CdS / ZnCr2O4 photocatalyst as well as preparation method and application thereof
By constructing the heterojunction of CdS/ZnCr2O4 composite materials, the problems of low yields in the aldehyde oxidation amidation reaction and difficulty in catalyst separation are solved, and an efficient, low-cost and environmentally friendly aldehyde oxidation amidation reaction are achieved.
Patent Information
- Application Number
- CN202411503601.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing photocatalysts have problems such as low yield, high oxygen demand, expensive catalysts or need additives in the aldehyde oxidation amidation reaction, and the separation of homogeneous photocatalysts is difficult.
CdS/ZnCr2O4 composite material is used as a heterogeneous photocatalyst to form heterojunctions through solvothermal reactions, and is used for aldehyde oxidation amidation reaction. The catalyst can achieve high yields under air and visible conditions.
The high yield of aldehyde oxidation amidation reaction is achieved, the catalyst is easy to separate, low cost, environmentally friendly, and has industrial prospects.
Smart Images

Figure CN119425733A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material preparation and catalytic synthesis, and in particular to a CdS / ZnCr2O4 photocatalyst and a preparation method and application thereof. Background Art
[0002] Visible light-mediated photoredox catalysis has become a green synthetic strategy. Compared with homogeneous catalysts such as transition metal complexes of ruthenium or iridium and various organic dyes, photoredox catalysis using heterogeneous photocatalysts has the inherent advantage of easy catalyst separation and recovery, which has aroused great interest in both industry and academia. Amides are important in organic synthesis as the structural skeleton of proteins and peptides, key functional groups in natural products and drugs. Direct cross-dehydrogenative coupling of aldehydes with amines is one of the most economical methods for preparing amides. There are many methods for forming amide bonds using aldehydes and amines as starting materials, but traditional syntheses require the use of expensive transition metal catalysts, high temperatures or excessive use of strong oxidants. At present, there have been some reports at home and abroad. For example, in the literature (Asian J.Org.Chem.2019,8,1411-1414), an aldehyde oxidative amidation reaction under oxygen conditions was achieved by using anthraquinone as a photocatalyst, but the yield was low and the demand for oxygen made industrialization difficult; in the literature (Org.Biomol.Chem.2016,14,7028-7037), boron dipyrrolidone was used as a photocatalyst to achieve aldehyde oxidative amidation reaction under air conditions, but additional 2,6-di-tert-butyl-p-cresol was required. Most existing methods involve the use of expensive catalysts or require additives, and the separation of homogeneous photocatalysts is still problematic. Summary of the invention
[0003] The present invention aims at the deficiencies of the prior art and provides a CdS / ZnCr2O4 photocatalyst and a preparation method and application thereof. The heterogeneous photocatalyst can be used for photocatalytic aldehyde oxidative amidation reaction, and a high yield can be achieved with a low amount of catalyst under air and visible light conditions. The catalyst has low cost, high activity, and is environmentally friendly, and has industrial prospects.
[0004] ZnCr2O4 is a typical chromium-based spinel semiconductor, which is widely used in gas sensing, humidity sensing, synthesis gas conversion, adsorption, etc. However, the large energy band width and poor stability limit the application of ZnCr2O4 in photocatalysis. The present invention combines it with CdS with good visible light absorption performance to obtain a CdS / ZnCr2O4 composite material with an optimal ratio, while reducing the carrier recombination rate in CdS. The obtained composite material has good electron-hole separation efficiency and can be used to efficiently realize photocatalytic aldehyde oxidation amidation reaction. The reaction can be carried out in air without other additives. The CdS / ZnCr2O4 composite material is easy to separate as a heterogeneous catalyst and has good industrial prospects.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A CdS / ZnCr2O4 photocatalyst is a binary composite material consisting of CdS nanorods and ZnCr2O4 nanoparticles, wherein the ZnCr2O4 nanoparticles are on the surface of the CdS nanorods.
[0007] Preferably, the CdS nanorods and ZnCr2O4 nanoparticles form a heterojunction through a solvothermal reaction.
[0008] Further preferably, the CdS nanorods and ZnCr2O4 nanoparticles are 2+ The CdS nanorods and ZnCr2O4 nanoparticles containing heterojunctions were formed by the solvent thermal reaction of the source and thiourea.
[0009] Preferably, the CdS / ZnCr2O4 photocatalyst can be used for photocatalytic aldehyde oxidative amidation reaction.
[0010] The preparation method of the above-mentioned CdS / ZnCr2O4 photocatalyst comprises the following steps:
[0011] (1) Cr 6+ Source, Zn 2+ The source, water and ethylene glycol are mixed and stirred to form a dispersion, and a solvent thermal reaction is carried out. After the reaction is completed, the dispersion is washed and dried, and then high-temperature calcination is carried out to obtain ZnCr2O4 nanoparticles.
[0012] (2) The ZnCr2O4 nanoparticles and Cd 2+ The source, thiourea and ethylenediamine are mixed and stirred to form a dispersion, and a solvent thermal reaction is carried out. After the reaction is completed, the dispersion is washed and dried to obtain a CdS / ZnCr2O4 photocatalyst.
[0013] Preferably, the Cr in step (1) 6+Source, Zn 2+ The dispersion formed by mixing the source, water and ethylene glycol is: Cr 6+ The source is dissolved in water and added dropwise to the solution containing Zn 2+ In the ethylene glycol of the source;
[0014] Preferably, in step (1), Cr 6+ Cr in the source 6+ and Zn 2+ Zn in the source 2+ The molar ratio is 3-1:3-1;
[0015] Further preferably, the Cr in step (1) 6+ Cr in the source 6+ and Zn 2+ Zn in the source 2+ The molar ratio is 3-1:1;
[0016] Preferably, the volume ratio of water to ethylene glycol in step (1) is 2-20:2-20;
[0017] Further preferably, the volume ratio of water to ethylene glycol in step (1) is 5-15:5-15;
[0018] Preferably, in step (1), Cr 6+ The mass volume ratio of source and water is 2-5g:2-20mL;
[0019] Further preferably, in step (1), the Cr 6+ The mass volume ratio of source and water is 2-4g:2-15mL;
[0020] Preferably, the stirring time in step (1) is 10-60 min;
[0021] Further preferably, the stirring time in step (1) is 20-50 min;
[0022] Preferably, the temperature of the solvent thermal reaction in step (1) is 100-200° C., and the time of the solvent thermal reaction is 12-36 h;
[0023] Further preferably, the temperature of the solvothermal reaction in step (1) is 120-180° C., and the time of the solvothermal reaction is 15-32 h;
[0024] Preferably, in step (1), Cr 6+ The source is K2Cr2O7 or K2CrO4; the Zn 2+ The source is ZnCl2;
[0025] Preferably, the high temperature calcination in step (1) refers to calcination in air;
[0026] Preferably, the high-temperature calcination in step (1) is carried out in a tubular furnace.
[0027] Preferably, the heating rate of the high-temperature calcination in step (1) is 2-10°C / min; the temperature of the high-temperature calcination is 400-700°C; and the time of the high-temperature calcination is 1-6h.
[0028] Preferably, the washing method in step (1) is to use ultrapure water for 3-5 times and ethanol for 3-5 times; the drying is performed at 40-100° C., oven drying or vacuum drying, and the drying time is more than 6 hours;
[0029] Preferably, the water in step (1) is ultrapure water;
[0030] Preferably, the ZnCr2O4 nanoparticles, Cd 2+ Cd in source 2+ The dosage ratio (mass, molar amount, mass) of thiourea is 10-150 mg: 0.1-2 mmol: 200-500 mg;
[0031] Further preferably, in step (2), the ZnCr2O4 nanoparticles, Cd 2+ Cd in source 2+ The dosage ratio (mass, molar amount, mass) of thiourea is 20-100 mg: 0.5-2 mmol: 250-450 mg;
[0032] Further preferably, in step (2), the ZnCr2O4 nanoparticles, Cd 2+ Cd in source 2+ The dosage ratio (mass, molar amount, mass) of thiourea is 20-150 mg (20 mg, 23 mg, 46 mg, 70 mg, 93 mg, 116 mg, 150 mg, etc.): 1.25 mmol: 250-450 mg;
[0033] Preferably, in step (2), the ethylenediamine and Cd 2+ The volume-to-mass ratio of the source is 5-25 mL: 0.2-1 g;
[0034] Further preferably, in step (2), the ethylenediamine and Cd 2+ The volume-to-mass ratio of the source is 5-20 mL: 0.2-0.8 g;
[0035] Preferably, the stirring time in step (2) is 10-60 min;
[0036] Further preferably, the stirring time in step (2) is 20-60 min;
[0037] Preferably, the temperature of the solvent thermal reaction in step (2) is 100-200° C., and the time of the solvent thermal reaction is 12-36 h;
[0038] Further preferably, the temperature of the solvothermal reaction in step (2) is 120-200° C., and the time of the solvothermal reaction is 12-30 h;
[0039] Preferably, in step (2), Cd 2+ The source is Cd(NO3)2·4H2O.
[0040] Preferably, the washing method in step (2) is to use ultrapure water for 3-5 times and ethanol for 3-5 times; the drying is performed at 40-100° C., oven drying or vacuum drying, and the drying time is more than 6 hours;
[0041] Application of the above CdS / ZnCr2O4 photocatalyst in photocatalytic organic reactions.
[0042] Preferably, the photocatalytic organic reaction is a photocatalytic aldehyde oxidative amidation reaction;
[0043] Preferably, the photocatalytic organic reaction is carried out under light.
[0044] Preferably, the CdS / ZnCr2O4 photocatalyst is used for photocatalytic aldehyde oxidative amidation reaction, comprising the following steps:
[0045] Compound 1, compound 2 and CdS / ZnCr2O4 photocatalyst are dissolved in a solvent, and an aldehyde oxidative amidation reaction is carried out under light to obtain compound 3;
[0046] The general reaction formula is:
[0047]
[0048] Among them, R 1 is selected from substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl; R 2 , R 3 are each independently selected from substituted or unsubstituted alkyl, substituted or unsubstituted alkoxy, substituted or unsubstituted cycloalkyl, substituted or unsubstituted heterocycloalkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, or R 2 , R 3 Together with the nitrogen atom, it forms a substituted or unsubstituted nitrogen-containing heterocycloalkyl group.
[0049] Further preferably, the number of substituents in the substituted alkyl, substituted alkoxy, substituted cycloalkyl, substituted heterocycloalkyl, substituted aryl, substituted heteroaryl, and substituted nitrogen-containing heterocycloalkyl is one or more, and the multiple substituents are the same or different; the substituents are one or more of hydrogen, cyano, nitro, halogen (fluorine, chlorine, bromine, iodine), alkyl (carbon number 1-10), and alkoxy (carbon number 1-10).
[0050] Further preferably, the number of carbon atoms of the alkyl group in the substituted or unsubstituted alkyl group is 1-10, the number of carbon atoms of the alkoxy group in the substituted or unsubstituted alkoxy group is 1-10, the number of carbon atoms of the cycloalkyl group in the substituted or unsubstituted cycloalkyl group is 3-10, the total number of carbon atoms and heteroatoms of the heterocycloalkyl group in the substituted or unsubstituted heterocycloalkyl group is 3-10, the number of carbon atoms of the aryl group in the substituted or unsubstituted aryl group is 6-12, the total number of carbon atoms and heteroatoms of the heteroaryl group in the substituted or unsubstituted heteroaryl group is 6-12, and the total number of carbon atoms and heteroatoms of the nitrogen-containing heterocycloalkyl group in the substituted or unsubstituted nitrogen-containing heterocycloalkyl group is 3-10.
[0051] More preferably, the number of carbon atoms of the aryl group in the substituted or unsubstituted aryl group is 6, and the total number of carbon atoms and heteroatoms of the heteroaryl group in the substituted or unsubstituted heteroaryl group is 6.
[0052] More preferably, the aryl group in the substituted or unsubstituted aryl group is a benzene ring.
[0053] Further preferably, the compound 1 is 4-cyanobenzaldehyde or a derivative thereof;
[0054] Further preferably, the illumination is visible light; and the conditions for the aldehyde oxidative amidation reaction include:
[0055] Air or oxygen; the aldehyde oxidative amidation reaction is carried out at room temperature;
[0056] Further preferably, the solvent is one or more of water, acetonitrile, N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, tetrahydrofuran and dioxane, and the volume molar ratio of the solvent to compound 1 is 5-15 mL / mmol;
[0057] More preferably, the volume molar ratio of the amount of the solvent to compound 1 is 8-15 mL / mmol;
[0058] Further preferably, the mass molar ratio of the dosage of the CdS / ZnCr2O4 photocatalyst to the compound 1 is 5-35 mg / mmol; and the molar ratio of the compound 1 to the compound 2 is 1-5:1-5.
[0059] More preferably, the mass molar ratio of the dosage of the CdS / ZnCr2O4 photocatalyst to the compound 1 is 10-25 mg / mmol.
[0060] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0061] (1) The present invention effectively improves the separation efficiency and transmission rate of photogenerated carriers of the catalyst by constructing a heterojunction, thereby having high catalytic activity;
[0062] (2) The CdS / ZnCr2O4 photocatalyst prepared by the present invention can be used as a highly efficient photocatalyst to achieve aldehyde oxidative amidation reaction;
[0063] (3) The raw materials of the present invention are cheap and readily available, with low investment and high returns;
[0064] (4) The reaction conditions of the present invention are simple, and large-scale batch production of aldehyde oxidative amidation can be easily achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 This is a scanning electron microscope image of the CdS / ZnCr2O4 photocatalyst prepared in Example 1 of the present invention.
[0066] Figure 2 2 are XRD patterns of CdS, ZnCr2O4 and CdS / ZnCr2O4 photocatalysts prepared in Examples 1, 6 and 7 of the present invention.
[0067] Figure 3-7 This is the NMR spectrum of the compound obtained in the reaction of Example 1 of the present invention. DETAILED DESCRIPTION
[0068] The present invention is further described in detail with reference to the following examples, but the embodiments of the present invention are not limited thereto. For process parameters not specifically noted, conventional techniques can be used. Reagents or instruments used without indicating the manufacturer are considered to be conventional products that can be purchased commercially.
[0069] Example 1
[0070] (1) 3.88 g of K2CrO4 was ultrasonically dissolved in 12.5 mL of pure water, and 1.36 g of ZnCl2 was ultrasonically dissolved in 12.5 mL of ethylene glycol. The K2CrO4 solution was then added dropwise to the ZnCl2 solution, stirred at room temperature for 30 min, transferred to a polytetrafluoroethylene liner, and subjected to a solvothermal reaction in a reactor at 150 °C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60 °C for 12 h. Finally, the obtained solid was placed in a tube furnace, heated to 600 °C at a rate of 5 °C / min in air, and calcined for 2 h to obtain ZnCr2O4 nanoparticles;
[0071] (2) Add the ZnCr2O4 nanoparticles (70 mg) described in step (1), 384 mg of Cd(NO3)2·4H2O, 284 mg of thiourea and 10 mL of ethylenediamine into a polytetrafluoroethylene liner and stir for 30 min to form a uniform suspension. Then, a solvothermal reaction was carried out in a reactor at 180°C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, and the bright yellow precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60°C for 12 h to obtain a CdS / ZnCr2O4 photocatalyst;
[0072] The scanning electron microscopy of the CdS / ZnCr2O4 photocatalyst obtained in this example is as follows Figure 1 As shown, the XRD pattern of CdS / ZnCr2O4 photocatalyst is as follows Figure 2 This confirms the composition and morphology of the synthesized material.
[0073] The CdS / ZnCr2O4 photocatalyst obtained in this example is used for aldehyde oxidative amidation reaction, and the specific steps are as follows:
[0074] 26 mg 4-cyanobenzaldehyde, 50 μL pyrrolidine, 2 mL tetrahydrofuran (THF) and 4 mg CdS / ZnCr2O4 photocatalyst were added to a flask and reacted for 14 h under irradiation with a light source (40 W blue LED). After the reaction, 4-(pyrrolidine-1-carbonyl)benzonitrile (3a) was obtained by column chromatography with a yield of 94% (see Table 1). The H NMR spectrum of the product is shown in FIG. Figure 3 The result characterization data is shown as follows:
[0075]
[0076] 4-(pyrrolidine-1-carbonyl)benzonitrile(3a)
[0077] Yield: 37.6 mg (94%);1 H NMR (500MHz, CDCl3) δ7.69 (d, J = 8.0Hz, 2H),
[0078] 7.60(d,J=8.0Hz,2H),3.64(t,J=7.0Hz,2H),3.36(t,J=6.6Hz,2H),2.00-1.94(m,2H),1.93-1.87(m,2H).
[0079] 20 μL benzaldehyde, 50 μL pyrrolidine, 2 mL tetrahydrofuran (THF) and 4 mg CdS / ZnCr2O4 photocatalyst were added to a flask and reacted for 24 h under irradiation with a light source (40 W blue LED). After the reaction, phenyl (pyrrolidin-1-yl) ketone (3b) was obtained by column chromatography with a yield of 62%. The H NMR spectrum of the product is shown in FIG. Figure 4 The result characterization data is shown as follows:
[0080]
[0081] phenyl(pyrrolidin-1-yl)methanone(3b)
[0082] Yield: 21.7 mg (62%); 1 H NMR (500MHz, CDCl3) δ7.52-7.50(m,2H),7.40(d,J=6.5Hz,3H),3.65(t,J=7.0Hz,2H),3.43(t,J=6.6Hz,2H),2.00-1.93(m,2H),1.90-1.85(m,2H).
[0083] 29 mg of p-chlorobenzaldehyde, 50 μL of pyrrolidine, 2 mL of tetrahydrofuran (THF) and 4 mg of CdS / ZnCr2O4 photocatalyst were added to a flask and reacted for 24 h under irradiation with a light source (40 W blue LED). After the reaction, (4-chlorophenyl)(pyrrolidin-1-yl)methanone (3c) was obtained by column chromatography with a yield of 89%. The H NMR spectrum of the product is shown in FIG. Figure 5 The result characterization data is shown as follows:
[0084]
[0085] 4-chlorophenyl)(pyrrolidin-1-yl)methanone(3c)
[0086] Yield: 37.2 mg (89%); 1H NMR (500MHz, CDCl3) δ7.47 (d, J = 8.4Hz, 2H),
[0087] 7.38(d,J=8.4Hz,2H),3.64(t,J=7.0Hz,2H),3.42(t,J=6.6Hz,2H),2.00-1.94(m,2H),1.91-1.86(m,2H).
[0088] 24 μL of p-methoxybenzaldehyde, 50 μL of pyrrolidine, 2 mL of tetrahydrofuran (THF) and 4 mg of CdS / ZnCr2O4 photocatalyst were added to a flask and reacted for 24 h under irradiation with a light source (40 W blue LED). After the reaction, (4-methoxyphenyl)(pyrrolidin-1-yl)methanone (3d) was obtained by column chromatography with a yield of 60%. The H NMR spectrum of the product is shown in FIG. Figure 6 The result characterization data is shown as follows:
[0089]
[0090] (4-methoxyphenyl)(pyrrolidin-1-yl)methanone(3d)
[0091] Yield: 24.6 mg (59%); 1 H NMR (500MHz, CDCl3) δ7.56-7.46 (m, 2H), 6.90 (d, J = 8.8Hz, 2H), 3.83 (s, 3H), 3.6 4(t,J=7.0Hz,2H),3.48(t,J=6.6Hz,2H),1.97-1.93(m,2H),1.89-1.86(m,2H).
[0092] 26 mg 4-cyanobenzaldehyde, 53 μL morpholine, 2 mL tetrahydrofuran (THF) and 4 mg CdS / ZnCr2O4 photocatalyst were added to a flask and reacted for 18 h under irradiation with a light source (40 W blue LED). After the reaction, 4-(morpholine-4-carbonyl)benzonitrile (3e) was obtained by column chromatography with a yield of 90%. The H NMR spectrum of the product is shown in FIG. Figure 7 The result characterization data is shown as follows:
[0093]
[0094] 4-(morpholine-4-carbonyl)benzonitrile(3e)
[0095] Yield: 38.9 mg (90%); 1H NMR (500MHz, CDCl3) δ7.72 (d, J = 8.2Hz, 2H),
[0096] 7.50(d,J=8.2Hz,2H),3.77(s,4H),3.62(s,2H),3.37(s,2H).
[0097] Example 2
[0098] (1) 3.88 g of K2CrO4 was ultrasonically dissolved in 12.5 mL of pure water, and 1.36 g of ZnCl2 was ultrasonically dissolved in 12.5 mL of ethylene glycol. The K2CrO4 solution was then added dropwise to the ZnCl2 solution, stirred at room temperature for 30 min, transferred to a polytetrafluoroethylene liner, and subjected to a solvothermal reaction in a reactor at 150 °C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60 °C for 12 h. Finally, the obtained solid was placed in a tube furnace, heated to 600 °C at a rate of 5 °C / min in air, and calcined for 2 h to obtain ZnCr2O4 nanoparticles;
[0099] (2) Add the ZnCr2O4 nanoparticles (23 mg) described in step (1), 384 mg of Cd(NO3)2·4H2O, 284 mg of thiourea and 10 mL of ethylenediamine into a polytetrafluoroethylene liner and stir for 30 min to form a uniform suspension. Then, a solvothermal reaction was carried out in a reactor at 180°C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, and the bright yellow precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60°C for 12 h to obtain a CdS / ZnCr2O4 photocatalyst;
[0100] The CdS / ZnCr2O4 photocatalyst obtained in this example is used for aldehyde oxidative amidation reaction, and the specific steps are as follows:
[0101] 26 mg 4-cyanobenzaldehyde, 50 μL pyrrolidine, 2 mL tetrahydrofuran (THF) and 4 mg CdS / ZnCr2O4 photocatalyst were added to a flask and reacted for 14 h under irradiation with a light source (40 W blue LED). After the reaction, 4-(pyrrolidine-1-carbonyl)benzonitrile (3a) was separated by column chromatography with a yield of 59% (see Table 1).
[0102] Example 3
[0103] (1) 3.88 g of K2CrO4 was ultrasonically dissolved in 12.5 mL of pure water, and 1.36 g of ZnCl2 was ultrasonically dissolved in 12.5 mL of ethylene glycol. The K2CrO4 solution was then added dropwise to the ZnCl2 solution, stirred at room temperature for 30 min, transferred to a polytetrafluoroethylene liner, and subjected to a solvothermal reaction in a reactor at 150 °C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60 °C for 12 h. Finally, the obtained solid was placed in a tube furnace, heated to 600 °C at a rate of 5 °C / min in air, and calcined for 2 h to obtain ZnCr2O4 nanoparticles;
[0104] (2) Add the ZnCr2O4 nanoparticles (46 mg) described in step (1), 384 mg of Cd(NO3)2·4H2O, 284 mg of thiourea and 10 mL of ethylenediamine into a polytetrafluoroethylene liner and stir for 30 min to form a uniform suspension. Then, a solvothermal reaction was carried out in a reactor at 180°C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, and the bright yellow precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60°C for 12 h to obtain a CdS / ZnCr2O4 photocatalyst;
[0105] The CdS / ZnCr2O4 photocatalyst obtained in this example is used for aldehyde oxidative amidation reaction, and the specific steps are as follows:
[0106] 26 mg of 4-cyanobenzaldehyde, 50 μL of pyrrolidine, 2 mL of tetrahydrofuran (THF) and 4 mg of CdS / ZnCr2O4 photocatalyst were added to a flask and reacted for 14 h under irradiation with a light source (40 W blue LED). After the reaction, 4-(pyrrolidine-1-carbonyl)benzonitrile (3a) was separated by column chromatography with a yield of 85% (see Table 1).
[0107] Example 4
[0108] (1) 3.88 g of K2CrO4 was ultrasonically dissolved in 12.5 mL of pure water, and 1.36 g of ZnCl2 was ultrasonically dissolved in 12.5 mL of ethylene glycol. The K2CrO4 solution was then added dropwise to the ZnCl2 solution, stirred at room temperature for 30 min, transferred to a polytetrafluoroethylene liner, and subjected to a solvothermal reaction in a reactor at 150 °C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60 °C for 12 h. Finally, the obtained solid was placed in a tube furnace, heated to 600 °C at a rate of 5 °C / min in air, and calcined for 2 h to obtain ZnCr2O4 nanoparticles;
[0109] (2) Add the ZnCr2O4 nanoparticles (93 mg) described in step (1), 384 mg of Cd(NO3)2·4H2O, 284 mg of thiourea and 10 mL of ethylenediamine into a polytetrafluoroethylene liner and stir for 30 min to form a uniform suspension. Then, a solvothermal reaction was carried out in a reactor at 180°C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, and the bright yellow precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60°C for 12 h to obtain a CdS / ZnCr2O4 photocatalyst;
[0110] The CdS / ZnCr2O4 photocatalyst obtained in this example is used for aldehyde oxidative amidation reaction, and the specific steps are as follows:
[0111] 26 mg 4-cyanobenzaldehyde, 50 μL pyrrolidine, 2 mL tetrahydrofuran (THF) and 4 mg CdS / ZnCr2O4 photocatalyst were added to a flask and reacted for 14 h under irradiation with a light source (40 W blue LED). After the reaction, 4-(pyrrolidine-1-carbonyl)benzonitrile (3a) was separated by column chromatography with a yield of 93% (see Table 1).
[0112] Example 5
[0113] (1) 3.88 g of K2CrO4 was ultrasonically dissolved in 12.5 mL of pure water, and 1.36 g of ZnCl2 was ultrasonically dissolved in 12.5 mL of ethylene glycol. The K2CrO4 solution was then added dropwise to the ZnCl2 solution, stirred at room temperature for 30 min, transferred to a polytetrafluoroethylene liner, and subjected to a solvothermal reaction in a reactor at 150 °C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60 °C for 12 h. Finally, the obtained solid was placed in a tube furnace, heated to 600 °C at a rate of 5 °C / min in air, and calcined for 2 h to obtain ZnCr2O4 nanoparticles;
[0114] (2) Add the ZnCr2O4 nanoparticles (116 mg) described in step (1), 384 mg of Cd(NO3)2·4H2O, 284 mg of thiourea and 10 mL of ethylenediamine into a polytetrafluoroethylene liner and stir for 30 min to form a uniform suspension. Then, a solvothermal reaction was carried out in a reactor at 180°C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, and the bright yellow precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60°C for 12 h to obtain a CdS / ZnCr2O4 photocatalyst;
[0115] The CdS / ZnCr2O4 photocatalyst obtained in this example is used for aldehyde oxidative amidation reaction, and the specific steps are as follows:
[0116] 26 mg of 4-cyanobenzaldehyde, 50 μL of pyrrolidine, 2 mL of tetrahydrofuran (THF) and 4 mg of CdS / ZnCr2O4 photocatalyst were added to a flask and reacted for 14 h under irradiation with a light source (40 W blue LED). After the reaction, 4-(pyrrolidine-1-carbonyl)benzonitrile (3a) was separated by column chromatography with a yield of 80% (see Table 1).
[0117] Example 6
[0118] (1) 3.88 g of K2CrO4 was ultrasonically dissolved in 12.5 mL of pure water, and 1.36 g of ZnCl2 was ultrasonically dissolved in 12.5 mL of ethylene glycol. The K2CrO4 solution was then added dropwise to the ZnCl2 solution, stirred at room temperature for 30 min, transferred to a polytetrafluoroethylene liner, and subjected to a solvothermal reaction in a reactor at 150 °C for 24 h. After the reaction, the mixture was naturally cooled to room temperature, the precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60 °C for 12 h. Finally, the obtained solid was placed in a tube furnace, heated to 600 °C at a rate of 5 °C / min in air, and calcined for 2 h to obtain a ZnCr2O4 photocatalyst;
[0119] The ZnCr2O4 photocatalyst obtained in this example is used for aldehyde oxidative amidation reaction, and the specific steps are as follows:
[0120] 26 mg 4-cyanobenzaldehyde, 50 μL pyrrolidine, 2 mL tetrahydrofuran (THF) and 4 mg ZnCr2O4 photocatalyst were added to a flask and reacted for 14 h under irradiation with a light source (40 W blue LED). After the reaction, 4-(pyrrolidine-1-carbonyl)benzonitrile (3a) was separated by column chromatography with a yield of 20% (see Table 1).
[0121] Example 7
[0122] (1) 384 mg of Cd(NO3)2·4H2O, 284 mg of thiourea and 10 mL of ethylenediamine were added to a polytetrafluoroethylene liner and stirred for 30 min to form a uniform suspension. Then a solvothermal reaction was carried out in a reactor at 180°C for 24 h. After the reaction was completed, the mixture was naturally cooled to room temperature, and the bright yellow precipitate was collected by centrifugation, washed several times with ethanol and ultrapure water, and dried in an oven at 60°C for 12 h to obtain a CdS photocatalyst;
[0123] The CdS photocatalyst obtained in this example is used for aldehyde oxidative amidation reaction, and the specific steps are as follows:
[0124] 26 mg of 4-cyanobenzaldehyde, 50 μL of pyrrolidine, 2 mL of tetrahydrofuran (THF) and 4 mg of CdS photocatalyst were added to a flask and reacted for 14 h under irradiation with a light source (40 W blue LED). After the reaction, 4-(pyrrolidine-1-carbonyl)benzonitrile (3a) was separated by column chromatography with a yield of 38% (see Table 1).
[0125] Table 1
[0126]
[0127]
[0128] Standard conditions: 4-cyanobenzaldehyde (0.2 mmol), pyrrolidine (0.6 mmol), rt, 14 h, air, blue LED, NMR yield.
[0129] It can be seen that under the same conditions, the CdS / ZnCr2O4 prepared in Example 1 has the best catalytic effect, which proves that the present invention synthesizes a photocatalyst that can efficiently realize oxidative amidation of aldehydes.
[0130] The above embodiments are only used to explain the present invention and are not intended to limit the present invention in any form. Simplification, modification, substitution and combination of the above embodiments made by those skilled in the art without departing from the content of the technical solution of the present invention according to the spirit and technical principles of the present invention shall all fall within the scope of protection of the technical solution of the present invention.
Claims
1. A CdS / ZnCr2O4 photocatalyst, characterized in that: The CdS / ZnCr2O4 photocatalyst is a binary composite material, which is composed of CdS nanorods and ZnCr2O4 nanoparticles, wherein the ZnCr2O4 nanoparticles are on the surface of the CdS nanorods.
2. The method for preparing the CdS / ZnCr2O4 photocatalyst according to claim 1, characterized in that: The following steps are involved: (1) Cr 6+ Source, Zn 2+ The source, water and ethylene glycol are mixed and stirred to form a dispersion, and a solvent thermal reaction is carried out. After the reaction is completed, the dispersion is washed and dried, and then high-temperature calcination is carried out to obtain ZnCr2O4 nanoparticles. (2) The ZnCr2O4 nanoparticles and Cd 2+ The source, thiourea and ethylenediamine are mixed and stirred to form a dispersion, and a solvent thermal reaction is carried out. After the reaction is completed, the dispersion is washed and dried to obtain a CdS / ZnCr2O4 photocatalyst.
3. The preparation method according to claim 2, characterized in that: Cr described in step (1) 6+ Source, Zn 2+ The dispersion formed by mixing the source, water and ethylene glycol is: Cr 6+ The source is dissolved in water and added dropwise to the solution containing Zn 2+ In the ethylene glycol of the source; In step (1), Cr 6+ Cr in the source 6+ and Zn 2+ Zn in the source 2+ The molar ratio is 3-1:3-1; The volume ratio of water to ethylene glycol in step (1) is 2-20:2-20; In step (1), Cr 6+ The mass volume ratio of source and water is 2-5g:2-20mL; The stirring time in step (1) is 10-60 min; The temperature of the solvent thermal reaction in step (1) is 100-200° C., and the time of the solvent thermal reaction is 12-36 hours; In step (1), Cr 6+ The source is K2Cr2O7 or K2CrO4; the Zn 2+ The source is ZnCl2; The high temperature calcination in step (1) refers to calcination in air; The heating rate of the high-temperature calcination in step (1) is 2-10°C / min; the temperature of the high-temperature calcination is 400-700°C; and the time of the high-temperature calcination is 1-6h.
4. The preparation method according to claim 2, characterized in that: The ZnCr2O4 nanoparticles, Cd 2+ Cd in source 2+ The dosage ratio of thiourea is 10-150mg:0.1-2mmol:200-500mg; In step (2), ethylenediamine and Cd 2+ The volume-to-mass ratio of the source is 5-25 mL: 0.2-1 g; The stirring time in step (2) is 10-60 min; The temperature of the solvent thermal reaction in step (2) is 100-200° C., and the time of the solvent thermal reaction is 12-36 hours; In step (2), Cd 2+ The source is Cd(NO3)2·4H2O.
5. The preparation method according to claim 2, characterized in that: The drying in steps (1) and (2) is performed at 40-100° C., in an oven or in a vacuum, and the drying time is more than 6 hours; the washing method is to use ultrapure water for 3-5 times and ethanol for 3-5 times.
6. Use of the CdS / ZnCr2O4 photocatalyst according to claim 1 in photocatalytic organic reactions.
7. The use according to claim 6, characterized in that: The photocatalytic organic reaction is a photocatalytic aldehyde oxidative amidation reaction; the photocatalytic organic reaction is carried out under light.
8. The use according to claim 7, characterized in that: The CdS / ZnCr2O4 photocatalyst is used for photocatalytic aldehyde oxidative amidation reaction, comprising the following steps: Compound 1, compound 2 and CdS / ZnCr2O4 photocatalyst are dissolved in a solvent, and an aldehyde oxidative amidation reaction is carried out under light to obtain compound 3; The general reaction formula is: Among them, R 1 is selected from substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl; R 2 , R 3 are each independently selected from substituted or unsubstituted alkyl, substituted or unsubstituted alkoxy, substituted or unsubstituted cycloalkyl, substituted or unsubstituted heterocycloalkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, or R 2 , R 3 Together with the nitrogen atom, it forms a substituted or unsubstituted nitrogen-containing heterocycloalkyl group.
9. The use according to claim 8, characterized in that: The substituents in the substituted alkyl, substituted alkoxy, substituted cycloalkyl, substituted heterocycloalkyl, substituted aryl, substituted heteroaryl and substituted nitrogen-containing heterocycloalkyl are one or more of hydrogen, cyano, nitro, halogen, alkyl and alkoxy; the carbon number of the alkyl in the substituted or unsubstituted alkyl is 1-10, the carbon number of the alkoxy in the substituted or unsubstituted alkoxy is 1-10, the carbon number of the cycloalkyl in the substituted or unsubstituted cycloalkyl is 3-10, the total number of carbon atoms and heteroatoms of the heterocycloalkyl in the substituted or unsubstituted heterocycloalkyl is 3-10, the carbon number of the aryl in the substituted or unsubstituted aryl is 6-12, the total number of carbon atoms and heteroatoms of the heteroaryl in the substituted or unsubstituted heteroaryl is 6-12, and the total number of carbon atoms and heteroatoms of the nitrogen-containing heterocycloalkyl in the substituted or unsubstituted nitrogen-containing heterocycloalkyl is 3-10.
10. The use according to claim 8, characterized in that: The illumination is visible light; the conditions of the aldehyde oxidative amidation reaction include: air or oxygen; the aldehyde oxidative amidation reaction is carried out at room temperature; The solvent is one or more of water, acetonitrile, N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, tetrahydrofuran and dioxane, and the volume molar ratio of the solvent to the compound 1 is 5-15 mL / mmol; The mass molar ratio of the dosage of the CdS / ZnCr2O4 photocatalyst to the compound 1 is 5-35 mg / mmol; the molar ratio of the compound 1 to the compound 2 is 1-5:1-5.
Citation Information
Patent Citations
Preparation method and application of CdS / Znln2S4 heterojunction photocatalyst
CN115739123A
CdS / Bi / Ti3C2TX photocatalyst as well as preparation method and application thereof
CN117225436A
Oxygen vacancy doped nanorod composite material as well as preparation method and application thereof
CN118543361A